Infrastructure's Contribution to Aggregate Output - Canning, David 1988- (The World Bank, 1999)
Of the major kinds of physical infrastructure, electricity generating capacity has roughly the same marginal productivity as physical capital as a whole. So have roads-plus-rail, globally and in lower-income countries. Telephones, however, and transport routes in higher-income countries, have higher marginal productivity than other kinds of capital. - Using panel data for a cross-section of countries, Canning estimates an aggregate production function that includes infrastructure capital. He finds that: · The productivity of physical and human capital is close to the levels suggested by microeconomic evidence on their private returns. · Electricity generating capacity and transportation networks have roughly the same marginal productivity as capital as a whole. · Telephone networks appear to show higher marginal productivity than other types of capital. Panel data cointegration methods used in estimation take account of the nonstationary nature of the data, are robust to reverse causation, and allow for different levels of productivity and different short-run business-cycle and multiplier relationships across countries. This paper - a product of Public Economics, Development Research Group - is part of a larger effort in the group to study the impact of public expenditures. The study was funded by the Bank's Research Support Budget under the research project Infrastructure and Growth: A Multicountry Panel Study (RPO 680-89). The author may be contacted at d.canning@qub.ac.uk